LONG-TERM NEUROLOGICAL COMPLICATIONS OF RADIOTHERAPY FOR BRAIN TUMORS: PATHOGENESIS, DIAGNOSIS, AND CONTEMPORARY TREATMENT APPROACHES - Karimova Nargiza Sunnatillayevna; Nishanov Daniyar Anarbayevich (Western European Studies, 2026)
To determine the pathophysiological mechanisms, diagnostic approaches, and contemporary treatment strategies for long-term neurological complications of radiotherapy (RT) for brain tumors
Keywords: radiotherapy; brain tumors; radiation necrosis; cognitive impairment